2021
DOI: 10.1007/s00382-021-05742-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing precipitation extremes (1981–2018) and deep convective activity (2002–2018) in the Amazon region with CHIRPS and AMSU data

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 112 publications
(154 reference statements)
1
18
0
Order By: Relevance
“…Note that fire incidence is associated with SST anomalies, especially the warm phase of ENSO [21,33,55]. In recent decades, some studies have reported a high frequency of droughts and extreme rainfall in some Amazonian areas [38,82,86,92,96,97]. Some periods of extreme drought in 1997 and 1998 were related to the occurrence of El Niño events [98], as well as the drought recorded in 2010, which was related to El Niño events from previous years [99].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Note that fire incidence is associated with SST anomalies, especially the warm phase of ENSO [21,33,55]. In recent decades, some studies have reported a high frequency of droughts and extreme rainfall in some Amazonian areas [38,82,86,92,96,97]. Some periods of extreme drought in 1997 and 1998 were related to the occurrence of El Niño events [98], as well as the drought recorded in 2010, which was related to El Niño events from previous years [99].…”
Section: Discussionmentioning
confidence: 94%
“…The Amazon contains vast reserves of C but can experience major changes in rainfall patterns, mainly because of the influence of large-scale phenomena (ENSO, SST anomalies, and moisture transport anomalies; e.g., Marengo and Espinoza [38], Espinoza et al [29], Towner et al [36], Funatsu et al [86]) which affect C dynamics [81]. Herein, the results obtained for the El Niño drought period, such as in 2009 when the annual absorption rate of C/pixel was 0.050 kg C m −2 year −1 , showed no significant differences with those obtained for the La Niña drought period (cold phase of ENSO).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite-based data sets were also used in water balance approaches to evaluate long-term trends Heerspink et al, 2020;Pacada et al, 2020; X. Y. and monthly variations of runoff (Builes-Jaramillo & Poveda, 2018). In addition, hydrological extreme events have been reported in the Amazon basin during the last decades, which has been possible by using satellite-based rainfall estimates (Barichivich et al, 2018;Espinoza et al, , 2014Funatsu et al, 2021;Gloor et al, 2013;Marengo & Espinoza, 2016;Satyamurty, da Costa, Manzi, & Candido, 2013;Sena et al, 2012). Applications of precipitation databases to the understanding of the hydrologic cycle through modeling are described in Section 6.2.…”
Section: Precipitationmentioning
confidence: 99%
“…To date, most studies have focused on reporting the extent, causes and impacts of deforestation on ecosystems and climate change. Consequently, studies have reported worrying predictions of changes in mean annual precipitation [3,22,23], an increase in extreme droughts [24] or precipitation events [25], and changes in the beginning and end dates of the rainy season [26,27]. Beyond deforestation, recent studies also mention the severe degradation of the Amazon rainforest due to fire, timber logging and forest fragmentation [28].…”
Section: Introductionmentioning
confidence: 99%